Efeito dos procedimentos de modelo de mando e imitação vocal no estabelecimento de repertório de ecoicos em crianças com TEA - Menezes, Gessionete Ferreira de (2024)
Echoing sounds and phonemes is a fundamentally important skill for acquiring speech, expected within the first 12 months of an individual's life. Behavior analysis researchers have dedicated themselves to studying teaching procedures that enable the acquisition, maintenance, and expansion of new verbal repertoires in children with autism spectrum disorder (ASD), who often have difficulty emitting verbal responses, such as echoic responses. The present study proposed to carry out a comparison between mand model and vocal imitation procedures training for teaching the verbal operant echoic, focusing on strategies for maintaining the reinforcing value of the items used during both types of training. Two children with ASD and deficits in the vocal verbal repertoire participated in the study. The results indicate that both procedures were effective in teaching echoics to one of the participants, but not to the second. The mand model procedure, however, produced faster acquisition of echoic behavior than the vocal imitation procedure, although such results were not replicated in a second comparison. The participants’ initial repertoire and characteristics of the phonemes selected for training deserve to be considered as conditions that seemed to interfere with the results found